PENGARUH KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN CV.STELLA CATERING - Firnanda Rianof; Abdul Malik (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to determine and analyze the effect of interpersonal communication and work motivation on employee performance CV. Stella Catering. The sampling technique used a saturated sample of 40 respondents. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y = 6.448 + 0.353X1 + 0.527X2. In the partial test (t test) the interpersonal communication variable has a positive and significant effect on employee performance with a t-count value of 2.395 > t-table 2.026 and a significant value of 0.022 <0.05 and the work motivation variable has a positive and significant effect on employee performance with a t-value count is 3.495 > t table 2.026 and the significant value is 0.001 < 0.05. Simulative significant test results (F test) interpersonal communication and work motivation variables have a positive and significant effect on employee performance with a calculated F value of 70.552 > F table 3.25 and a significant value of 0.000 <0.05. The results of the coefficient of determination test (R2) obtained an R Square value of 0.792, meaning that the employee performance variable can be explained by 79.2% by interpersonal communication and work motivation variables, while the remaining 20.8% is explained by other variables not included in this study.